High Soil Test Phosphorus Effect on Corn Yield. Issue 5 (13th September 2018) - Wortmann, Charles; Shapiro, Charles; Shaver, Tim; Mainz, Michael
Abstract : Core Ideas: High soil test P levels are often recommended for high yield corn. Many states recommend a deficiency correction approach for P application. Application of P to replace removal in the previous harvest was marginally superior. Maintenance of Bray‐1 P at > 25 ppm was not justified. Phosphorus removal in crop harvest has increased as yields have increased. Fertilizer P use guidelines are based on calibrations often developed for much lower yield levels and may need recalibration. Corn yields may be greater with higher than recommended soil test P when springs are relatively wet and cool. Research was conducted across 12 irrigated and five rainfed site‐years in Nebraska with initial Bray‐1 P ≤ 11 mg kg –1 to evaluate P application strategies for yield and P uptake of continuous corn ( Zea mays L.) with and without tillage. The fertilizer P treatments were maintained on the same plots and included: (i) no P applied (0P); (ii) P applied according to the University of Nebraska‐Lincoln deficiency correction recommendation (UNL_P); (iii) P applied to replace P removed in the previous harvest (Replace_P); (iv) Bray‐1 P increased and maintained at 25 mg kg –1 (Bray_25); and (v) Bray‐1 P increased and maintained at 35 mg kg –1 (Bray_35). Interactions of P practice with other factors were not significant indicating consistency of P practice effects across varied climate conditions near planting and plant emergence. Grain yield was 9.3% and 0.89 Mg ha –1 more with the P‐applied treatments compared with 0P. Grain yield was 3.3% more due to the additional 5.9 kg ha –1 yr –1 P applied with Replace_P compared with UNL_P. Grain yield did not differ for Replace‐P, Bray_25, and Bray_35. Plant P uptake was on average linearly increased by 0.27 kg kg –1 P applied. Fertilizer P application for continuous corn should be by Replace_P.